3455 Association between Transfer of Children from the Emergency Department and Pediatric Readiness of the Hospital. (27th March 2019) - Lieng, Monica; Rosenthal, Jennifer; Sigal, Ilana; Dayal, Parul; Haynes, Sarah; Mouzoon, Jamie; Favila, Amanda; Marcin, James
Abstract : OBJECTIVES/SPECIFIC AIMS: As pediatric care becomes more concentrated in large urban hospitals, smaller rural hospitals with reduced pediatric care capacity may opt to transfer pediatric patients to higher levels of care even if the patient has a condition that is manageable in a general ED. Up to 20-40% of pediatric transfers are considered avoidable, placing a burden on the patient, their family and the health care system. The aim of this study is to determine the association between pediatric readiness (as measured by the National Pediatric Readiness Project score) and risk of interfacility transfer. We hypothesized that emergency departments with higher measures of pediatric readiness would be less likely to transfer pediatric patients to another facility. METHODS/STUDY POPULATION: The most recent and complete National Pediatric Readiness Project data were from 300 California hospitals in 2012. These data include the overall pediatric readiness score, presence of inter-facility guidelines (written protocols on patients needing care not available at the hospital), presence of interfacility agreements (written agreements with other hospitals regarding transfer patients), and other variables on the facility's capacity to care for pediatric patients. We linked these hospital data with patient encounter data from the California Office of Statewide Health Planning and Development Emergency Department (ED) Database (OSHPD) using hospital name and zip code. To be eligible for the study, the patient must have a documented ED encounter and be less than 18 years old during the encounter. A patient was considered a transfer patient if they were transferred to a separate general hospital, children's hospital, federal health care facility, rehabilitation facility, Critical Access Hospital or psychiatric hospital. Chi-square tests and t-tests were used for descriptive statistics. For non-normal data, we used the non-parametric Kruskall-Wallis test. We also used logistic regression to compare the odds of transfer between comparison groups. Statistical analyses were conducted in the R environment version 3.4.4. RESULTS/ANTICIPATED RESULTS: In 2012, there were 2, 604, 723 pediatric ED encounters, of which 10, 966 resulted in a transfer (0.4%). Transferred patients on average were older (15 vs. 5 years, p < 0.001) and more likely to be female (58.6% vs 46.6%, p < 0.001). The transfer group originated from hospitals with a lower median pediatric readiness score (76.0 vs 78.3, p < 0.001). Patients were less likely to be transferred if they were seen at a hospital with written guidelines with transfer protocols (OR 0.89, 95% CI 0.83—0.95, p < 0.001). Patients were more likely to be transferred if they were seen at a hospital with written interfacility agreements with other hospitals (OR 1.17, 95%CI 1.10—1.25, p < 0.001). We anticipate, that even with more sophisticated multilevel statistical models, pediatric readiness scores will remain associated with odds of transfer. DISCUSSION/SIGNIFICANCE OF IMPACT: These preliminary data suggest that hospitals with higher levels of pediatric readiness and written guidelines with transfer protocols are less likely to transfer pediatric patients. There may be actionable policy and procedural items that a hospital could enact to lower the rate of transfer patients. Future analyses will include more complex statistical modeling to adjust for confounders, will include inpatient data, and will compare the risk of potentially avoidable transfers between hospitals with varying levels of pediatric readiness.